The rights of man and animal experimentation - Martin, J. (Journal of medical ethics, 1990)
Since emotions give contradictory signals about animal experimentation in medical science, man's relationship to animals must be based upon reason. Thomas Aquinas argues that man is essentially different from animals because man's intellectual processes show evidence of an abstract mechanism not possessed by animals. Man's rights arise in association with this essential difference. The consequence is that only man possesses true rights by Aquinas's definition; animals have them only by analogy. However, cruelty to animals is illicit and they should be protected, principally not because they have rights, but because he who is cruel to animals is more likely to be cruel to his fellowman. If there is a need for animal experimentation in science for the good of man, this approach gives philosophical justification for experimentation, since man's well-being must come before that of animals because of his unique possession of rights. However, those experiments should be carried out in the kindest way possible, to promote kindness towards man. To see man as solely part of a biological continuum in competition for rights with those beings close to him biologically, detracts from man's dignity.